ChemInform Abstract: A Metal‐Free and Microwave‐Assisted Efficient Synthesis of Diaryl Sulfones. Issue 33 (25th July 2013) - Kumar, Dalip; Arun, V.; Pilania, Meenakshi; Shekar, K. P. Chandra
Abstract Various sulfinates react with a broad spectrum of symmetrical or unsymmetrical diaryliodonium salts to give the corresponding sulfones.